2013
DOI: 10.4161/nucl.26226
|View full text |Cite
|
Sign up to set email alerts
|

How to build a yeast nucleus

Abstract: Biological functions including gene expression and DNA repair are affected by the 3D architecture of the genome, but the underlying mechanisms are still unknown. Notably, it remains unclear to what extent nuclear architecture is driven by generic physical properties of polymers or by specific factors such as proteins binding particular DNA sequences. The budding yeast nucleus has been intensely studied by imaging and biochemical techniques, resulting in a large quantitative data set on locus positions and DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 42 publications
(85 reference statements)
3
36
0
Order By: Relevance
“…First, the abundance of intra-arm interactions in Drosophila may also be dictated by robust homolog pairing that competes away non-homologous contacts 61 . Second, chromosome organization in the yeast nucleus can be explained by the confinement of chromosomes and tethering of chromosome centromere and telomere to the NE 14,15 . Finally, non-specific (entropic) forces can drive the self-organization of polymers 38,51,57,62 .…”
Section: Chr-ne Attachments Affect Whole-chromosome and Chromosome Armentioning
confidence: 99%
See 3 more Smart Citations
“…First, the abundance of intra-arm interactions in Drosophila may also be dictated by robust homolog pairing that competes away non-homologous contacts 61 . Second, chromosome organization in the yeast nucleus can be explained by the confinement of chromosomes and tethering of chromosome centromere and telomere to the NE 14,15 . Finally, non-specific (entropic) forces can drive the self-organization of polymers 38,51,57,62 .…”
Section: Chr-ne Attachments Affect Whole-chromosome and Chromosome Armentioning
confidence: 99%
“…Heterogeneous interaction models allow affinity for the NE to vary along the chromosome fiber; several Downloaded by [UQ Library] at 01: 10 15 June 2015 models have specifically investigated the effects of chromosome tethers positioned at the centromeres and telomeres 11,12,14,15,[17][18][19] . These studies in yeast have led to several predictions: the 3D position of a gene can be altered due to the presence of an NE tether positioned within 10 kb 11 ; removal of chromosomal tethers at the centromere increases chromosome mobility as quantified by its confinement radius 18 ; the presence of Chr-NE tethers affects the distribution of telomere-telomere distances 17 ; the position of chromosomes within the nucleus may be altered due to a combination of Chr-NE tethering and volume exclusion 12 ; and the distribution of distances between the spindle pole body and the silent mating locus depends on tethering at the telomere 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations have been extended by the use of chromosome conformation capture approaches (3,4) to map the relative positions of loci along each chromosome based on their frequencies of crosslinking (contact frequencies) with many other sites in the genome. Previous studies have shown that telomere-associated sequences preferentially recombine with other telomere-associated loci whereas centromere-linked sites selectively recombine with other centromere-linked loci (5)(6)(7). However, such preferences, presumably caused by the constraints of tethering, may not reflect the general behavior of most sequences undergoing homologous recombination.…”
mentioning
confidence: 95%